Spatial and temporal patterns of Kruppel gene expression in early Drosophila embryos. - Knipple, D.C.; Seifert, E.; Rosenberg, U.B.; Preiss, A.; Jäckle, H. (Nature, 1985)
The Krüppel (Kr) locus is a member of the 'gap' class of segmentation genes of Drosophila melanogaster. Mutations at the Kr locus cause the deletion of contiguous segments from the embryonic body pattern. We have elucidated the spatial and temporal characteristics of Kr gene expression during early embryo development, the localization of cytoplasmic Kr+ activity and its spatial requirement for normal segmentation.